Comparing the Efficacy of Non-Instrumented Versus Instrumented Fusion in Anterior Cervical Discectomy - Badar Uddin Ujjan, Amajd Ali Qureshi, Abdul Rauf Mughal, Tahir Shahab, Imran Jawaid, Bashir Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: to compare the efficacy of management plans for anterior cervical decompression with non-instrumental and instrumental fusion procedures for reducing pain, improving recovery, and assessing complications in cervical degenerative diseases. Methodology: Study was randomized controlled trial registered under Iranian Registry of Clinical Trials [81024] conducted at the Department of Neurosurgery, Gambat Institute of Medical Sciences, Gambat, Pakistan from June 2022 to May 2023. The trial enrolled patients diagnosed with degenerative cervical disease. Pre-operative assessments included VAS scores. Post-surgery, VAS scores were monitored at 3 months, with 50% reduction in pain score (VAS) was labeled as effective pain relief. Post operative hematoma formation, hospital stay were also monitored. Results: The recovery was excellent in 15 (65.2%) patients of ACD whereas the recovery was excellent in 13 (44.8%) patients of ACDF Group. (p=0.327). The mean preoperative VAS score at 3 months of ACD and ACDF groups was 8.65±0.88 and 8.34±0.67, respectively. (p=0.160). The mean length of hospital stays of ACD and ACDF groups was 6.91±1.68 days and 7.24±1.53 days, respectively. (p=0.464). Conclusion: Both procedures, with and without fusion, demonstrate good to excellent outcomes in functional recovery and relief in pain. They are comparable in terms of hospital stay length and postoperative complications. Keywords: Anterior cervical discectomy, instrumented fusion, non-instrumented, Recovery, Pain